Microclima e parâmetros fisiológicos de novilhas da raça holandês - Grunevald, Dieisson Gregory (2017)
The present study was subdivided into two trials. The first test had as objective to evaluate by means of indices of thermal comfort two distinct environments (free stall and picket) from 07:00 to 16:00 hours considering the sunny, partly cloudy and cloudy sky. The second objective was to evaluate the physiological parameters of Dutch heifers allocated to pickets with full sun exposure and free stall for two hours from 11:00, 12:00, 13:00 and 14:00 hours on non-consecutive days also considering the three types of sky coverage. The tests were carried out in the municipality of Marechal Cândido Rondon - PR, in the months of July and August of 2016. For the evaluation of the physiological parameters, nine heifers of the black and white Dutch breed were used, with mean age of 20 ± 3.5 months and mean body mass of 490 ± 64.12 kg and on average in the 5th month of pregnancy. The experimental design was completely randomized with time-repeated measures. The physiological variables evaluated were: Respiratory rate (RR), heart rate (HR), rectal temperature (RT) and surface temperature (ST). The data on air temperature, black globe temperature, relative humidity and wind speed were collected and used to determine the temperature and humidity index (THI), black globe humidity index (BGTI) and radiant heat load (RHL). In this study, it was verified that the free stall presented a more adequate thermal environment, especially when associated with cloud cover, presenting THI = 62, BGTI = 64 and RHL = 412 W m -2 when compared to full sun conditions with THI = 76, BGTI = 83 and RHL = 754 W m-2. The physiological parameters presented variation according to the moment of entry and the time of exposure to shade. However, they remained within normal limits for cattle, in all types of sky cover. The body surface temperature was the only physiological parameter that presented a strong positive correlation (r > 0.5) with THI, BGTI and RHL. The body surface temperature in dark fur areas of the animal was significantly higher (< 0.05) than that observed in light coat areas. There was no significant interaction for the time of entry and the dwell time in the shade between the types of sky cover, for none of the physiological parameters (HR, RR, ST and RT) evaluated. In this way, it can be concluded that although the thermal environment was characterized as critical, as shown in the thermal comfort indices, there were no significant alterations in the physiological parameters of the animals in the picket under a sunny condition in the afternoon.